Wirausahawan dan Muhammadiyah di Kampung Nitikan, Yogyakarta 1950-an-2000-an - Ghifari Yuristiadhi (Lembaran Sejarah, 2012)
The study examines the social and economic changes of the Nitikan society from the 1950s to 2000s. Nitikan is a kampong in the Yogyakarta area, one of the densely-populated cohorts of the oldest Islamic organization in Indonesia, the Muhammadiyah. It is shown that effective synergy (through membership and co-sponsored activities) between entrepreneurs and the Muhammadiyah organization resulted in the development of Nitikan as a businessmen’s center of a strong Muhammadiyah characteristics. In the end, this combination made Nitikan a successful role model of a civil society.